Burt Reynolds but enough about me - Reynolds, Burt 1936-2018 (Blink Publishing, 2015)
In But Enough About Me, legendary film actor and Hollywood superstar Burt Reynolds recall the people who shaped his life and career, for the better or for worse. From Cary Grant, Clint Eastwood and Robert Mitchum to Bette Davis, Marlon Brando and Liza Minelli, Burt pays homage to those he loves and respects, acknowledges those who've stayed loyal, and calls out the assholes he can't forgive. Recalling a life career spanning over 50 glorious years, Burt gives special attention to the two great loves of his life, Dinah Shore and Sally Field, his son Quinton as well as to the countless people who got in his way on his journey to Hollywood domination. With chapters on his early childhood, how he discovered acting, played poker, with Frank Sinatra, received directing advice from Orson Welles, his golden years in Hollywood, his comeback in the late 1990's, and how his life and art led him to found the Burt Reynolds Institute for Film and Theatre, But Enough About Me is the gripping and eye-opening story of one of cinema's true greats.--Description from inside book cover